Learning and Using Conversational Humor in a Second Language During Study Abroad. - Shively, Rachel (Language Play and Creativity Ser., 2018)
"This book examines the use of conversational humor in a second language in the context of study abroad. Using a longitudinal design, naturalistic interactions, and a language socialization framework, the study investigates the ways in which study abroad students develop in their production of humor in second language Spanish and discusses how those developments are the result of language learning processes grounded in social interaction"--